IMPLEMENTATION OF PROPHETIC EDUCATION IN PRIMARY EDUCATION INSTITUTIONS - Sholeh, Makherus (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2018)
Educational institutions are part of the social institutions that exist in society. It is a space between other social institutions that interact with each other, influencing, both reciprocal influences, unidirectional influences, and the influence of mutualist symbiosis. The mutual influence of institutions can actually be controlled by actors so that they can be optimized to accelerate the achievement of institutional goals. The social institutions in question in the view of the author can be categorized into two types, namely; macrocosmic and microcosmic. Prophetic from the word prophetic which means prophethood or concerning the prophet. The English word comes from the Greek